The Westing game - Raskin, Ellen (New York : Dutton Children's Books, 2003)
The mysterious death of an eccentric millionaire brings together an unlikely assortment of heirs who must uncover the circumstances of his death before they can claim their inheritance.
Cooperative Children's Book Center Choices, 2000-present
Boston Globe/Horn Book Award Winners
John Newbery Medal Winners
10-14.
5-9.
John Newbery Medal, 1979.